Complications of Labour in Obese Obstetric Patients - Gul, Hina; Shaikh, Shahida; Shaikh, Aqsa (Biological and Clinical Sciences Research Journal, 2025)
Obesity during pregnancy is a rising public health concern and has been linked to an increased risk of labor complications. Maternal obesity contributes to mechanical, hormonal, and metabolic alterations that affect the labor process, leading to higher rates of cesarean section, labor induction failure, prolonged labor, and maternal and neonatal morbidity. Objective: To assess the frequency and types of labor complications in obese obstetric patients and determine the associated maternal outcomes. Methods: This descriptive cross-sectional study included 169 obese pregnant women at Shaikh Zayed Women Hospital Larkana over a period of June 2024 December 2024. Detailed demographic data, obstetric history, and intrapartum parameters were recorded. Labor complications such as prolonged first/second stage, failed induction, shoulder dystocia, fetal distress, and mode of delivery were evaluated. Results: Out of 169 obese obstetric patients, 52.1% underwent cesarean delivery, with a significantly higher rate of failed induction in those with Class II/III obesity (39.0%) compared to Class I (20.7%, p = 0.01). Prolonged first stage of labor was observed in 46.8% of women with higher BMI. Maternal complications such as postpartum hemorrhage (28.6% vs. 12.0%, p = 0.005), wound infection (14.3% vs. 4.3%, p = 0.04), and prolonged hospital stay (19.5% vs. 6.5%, p = 0.03) were significantly more frequent in Class II/III obesity. Fetal distress, shoulder dystocia, and NICU admissions were also more common in this group, though not statistically significant. Conclusion: Obesity in pregnancy is significantly associated with an increased risk of labor complications, particularly cesarean delivery, prolonged labor, and failed induction.